The relationship between perceived teacher support and student engagement among higher vocational students: A moderated mediation model - Xu, Xiuni; Wu, Zhen; Wei, Dongpo (Frontiers in Psychology, 2023)
This study conducted a questionnaire on 1,136 higher vocational students using perceived teacher support, basic psychological needs satisfaction, learning drive,student engagement and Optimistic attributional styles for explaining positive events (OAS_P) five scales. This study explores the influence of higher vocational students perceived teacher support on student engagement, the mediation effect and the chain mediation effect of basic psychological needs satisfaction and learning drive, and the moderation effect of OAS_P. The results show that: (1) Perceived teacher support can indirectly predict the student engagement among higher vocational students through basic psychological needs satisfaction; (2) Perceived teacher support can indirectly predict student engagement through learning drive; (3) Perceived teacher support can indirectly predict student engagement through basic psychological needs satisfaction and learning drive; (4) OAS_P has a significant regulating effect on both learning drive and student engagement.